Connection Age with Behavior use Method Contraception Long Term in Active KB Acceptors in the Family Planning Village Program in Sungai Penuh City - Kiran Nandini; Vaulline Basyir; Firdawati; Rima Semiarty; Syamel Muhammad; Ilmiawati (Indonesian Journal of Advanced Research, 2024)
The Long Term Contraceptive Method (MKJP) is an effective contraceptive method used to plan, postpone, and terminate pregnancy. MKJP is considered effective because the failure rate is low compared to non-MKJP contraception. The factor of couples of childbearing age in using contraception cannot be separated from the behavioral factors of each individual. This research aims to determine the relationship between age and the behavior of using MKJP among active family planning acceptors in the family planning village program in Sungai Penuhcity. The design of this research is a cross-sectional study. The sample in this study was 354 people. Data was collected using a questionnaire and analyzed using chi-square. The research results showed a relationship between age (p= 0.003) and MKJP usage behavior.